Electrical and Optical Properties of Rectifying ZnO Homojunctions Fabricated by Wet Chemistry Methods. Issue 2 (6th December 2017) - Yatskiv, Roman; Tiagulskyi, Stanislav; Grym, Jan; Cernohorsky, Ondrej
Abstract : Rectifying ZnO homojunctions are fabricated by simple wet chemistry methods. The p–n junction is formed between a p‐type nanostructured seed layer deposited by sol–gel method on phosphorus doped Si substrates and an array of n‐type nanorods grown by chemical bath deposition. The p‐type conductivity in the nanostructured layer is achieved by thermal diffusion of phosphorus from the Si substrate. The diffusion of phosphorus is supported by the observation of optical transitions related to neutral acceptor bound exciton in low‐temperature photoluminescence spectra. The p–n junction shows a high value of rectification ratio. Charge transport through the p‐n junction is discussed in terms of non‐ideal interface. Abstract : A simple and low‐cost method for the preparation of highly rectifying ZnO p–n homojunctions formed between vertically oriented n‐type ZnO nanorods grown by chemical bath deposition and p‐type ZnO seed layers deposited by sol–gel method is demonstrated. The p‐type conductivity in the seed layers is achieved by thermal diffusion of phosphorus atoms from silicon substrate.